UPAYA PERAWATAN KEHAMILAN DENGAN SENAM HAMIL PADA IBU HAMIL TRIMESTER III DI PUSKESMAS AMBAN MANOKWARI - Nuryanti, Yayuk (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2021)
Pregnancy is a natural and physiological process that every woman experiences. Pregnant women are a high risk group for health problems. Stress is a health problem that often occurs in pregnant women. The goals of pregnancy exercise include reducing stress and preparing physically and psychologically for pregnant women. The purpose of the activity is to increase knowledge and empower pregnant women to care for their health independently. The method used is pregnancy exercise lectures and exercises. Participants in pregnancy exercise were 20 trimester III pregnant women. Implementing activities consisted of lecturers, health center midwives and students. The results of the activity were obtained through interviews which explained that participants learned about the benefits of pregnancy exercise, pregnancy exercise can make the body comfortable, and participants are interested in pregnancy exercise. The results of this activity can be concluded that the class of pregnant women must be held at the Puskesmas with activities such as pregnancy exercise.